2005
DOI: 10.1111/j.0013-9580.2005.47304.x
|View full text |Cite
|
Sign up to set email alerts
|

Kindling Limits the Interictal Neuronal Temporal Response Properties in Cat Primary Auditory Cortex

Abstract: Summary:Purpose: The present study examined the effect of electrical kindling on the interictal temporal response properties of single units recorded from primary auditory cortex (AI) of the adult cat.Methods: Cats were permanently implanted with electrodes in AI, kindled twice daily for 40 sessions, and the contralateral AI was subsequently mapped. Kindling stimulation consisted of 1-s trains of biphasic square-wave pulses applied at a frequency of 60 Hz, 100 µA above the afterdischarge (AD) threshold. The EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This is thought to reflect increased metabolic activity that is related to both local synaptic activity (Goense & Logothetis, 2008) as well as spiking activity (Lee et al., 2010; Young et al., 2011) and results in local increases in cerebral blood flow. Seizure‐induced changes to electrophysiologic measures such as enhanced evoked potentials (Teskey et al., 2002) and increased auditory unit responses to sound (Valentine et al., 2004, 2005) suggest that the increased fMRI signal to somatosensory stimulation is due, at least in part, to changes in local neural responsiveness. There was no change in the intensity of the activated voxels following seizures, indicating that changes in responsiveness to forepaw stimulation reflect a recruitment of neighboring sensory areas rather than simply an increase in blood flow to previously responsive areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to reflect increased metabolic activity that is related to both local synaptic activity (Goense & Logothetis, 2008) as well as spiking activity (Lee et al., 2010; Young et al., 2011) and results in local increases in cerebral blood flow. Seizure‐induced changes to electrophysiologic measures such as enhanced evoked potentials (Teskey et al., 2002) and increased auditory unit responses to sound (Valentine et al., 2004, 2005) suggest that the increased fMRI signal to somatosensory stimulation is due, at least in part, to changes in local neural responsiveness. There was no change in the intensity of the activated voxels following seizures, indicating that changes in responsiveness to forepaw stimulation reflect a recruitment of neighboring sensory areas rather than simply an increase in blood flow to previously responsive areas.…”
Section: Discussionmentioning
confidence: 99%
“…Because successful behavior relies on both motor and sensory information, altered sensory processing may contribute to the behavioral deficits seen following seizures. Regarding sensory processing, it has previously been shown in feline primary auditory neocortex that neuronal firing responses to various sounds are dramatically altered following experimentally induced repeated seizures in that structure (Valentine et al., 2004, 2005). Whether changes to the cortical processing of somatosensory information can be detected in response to experimentally elicited repeated seizures has not yet been reported.…”
mentioning
confidence: 99%
“…Synaptic plasticity is prominent among the mechanisms proposed to underlie changes in the topography of neocortical motor representations. Kindling induces robust synaptic potentiation in the pathways involved in seizure development (8,37,38) and results in alterations to spontaneous and evoked single‐unit activity (39–41).…”
Section: Discussionmentioning
confidence: 99%
“…One approach to understanding auditory plasticity is to use animal models, most commonly the rat and chinchilla, and study changes in auditory structures after damage to the periphery either through noise exposure (Abbott et al, 1999) or the use of ototoxic drugs (Hofstetter et al, 1997; Zhou et al, 2009). Many studies have shown cellular, molecular and electrophysiological changes at different sites in the auditory system in animals after hair cell loss (Wang et al, 1996; Benson et al, 1997; Abbott et al, 1999; Taggart et al, 2001; Wang et al, 2002; Norena and Eggermont, 2005; Valentine et al, 2005; D’Sa et al, 2007; Kraus et al, 2009; Fuentes-Santamaria et al, 2012; Fuentes-Santamaria et al, 2013; Baizer et al, 2015a). The differences of neurochemical profiles of neurons in humans and the experimental species suggest that the neurochemical correlates of the mechanisms of plasticity discovered in animals may not always translate directly to humans.…”
Section: Discussionmentioning
confidence: 99%